2023
DOI: 10.1136/bmjopen-2022-069334
|View full text |Cite
|
Sign up to set email alerts
|

Child and family experiences of a whole-systems approach to physical activity in a multiethnic UK city: a citizen science evaluation protocol

Abstract: IntroductionWhole-systems approaches are being adopted to tackle physical inactivity. The mechanisms contributing to changes resulting from whole-systems approaches are not fully understood. The voices of children and families that these approaches are designed for need to be heard to understand what is working, for whom, where and in what context. This paper describes the protocol for the children and families’ citizen science evaluation of the Join Us: Move, Play (JU:MP) programme, a whole-systems approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…This study identified key enablers, challenges, and reflections associated with the planning and implementation of the PEM; an innovative multi-faceted WSA to enable people who are inactive to move more through engaging multi-sectoral actors from across the health and social care system. As the practice of designing and implementing WSAs to address physical inactivity proliferates, it is important to explore what is being learnt by whom, where, and in what circumstances, and for such knowledge to be shared [ 55 ]. Indeed, the need for evidence to inform the operationalisation of WSAs has been acknowledged within the literature [ 26 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study identified key enablers, challenges, and reflections associated with the planning and implementation of the PEM; an innovative multi-faceted WSA to enable people who are inactive to move more through engaging multi-sectoral actors from across the health and social care system. As the practice of designing and implementing WSAs to address physical inactivity proliferates, it is important to explore what is being learnt by whom, where, and in what circumstances, and for such knowledge to be shared [ 55 ]. Indeed, the need for evidence to inform the operationalisation of WSAs has been acknowledged within the literature [ 26 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with literature that has detailed the use of co-production and involvement of service users as features of successfully implementing WSAs that address physical inactivity [ 31 , 33 ]. This is particularly important when service users are from marginalised and under-represented populations, such as the disabled people and people with long-term conditions, as included in the PEM [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have experienced challenges with recruiting/retaining adolescent study participants and therefore aim to interview adolescents with their parents as a dyad. While this approach may lead to limitations during data collection in phases 2 and 3 (eg, parents not wanting their child to participate, adolescents not wanting to discuss some topics in front of their parents or parent influence on responses),54 72 it may allow us to capture data on how vaccine decisions and behaviours are shaped within families. We will monitor participants completing our screening survey to determine if there are any under-represented groups (eg, males, younger and/or more vaccine hesitant parents) and develop more targeted recruitment strategies to boost recruitment from these groups as required.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
“…(Favilla et al, 2024), positing that science is an approach to contemplating and understanding the world that surrounds us. (Frazer et al, 2023) suggested that science is a method or procedure used to see the world around us to nd potential answers to our questions. The following opinion is expressed by (Ván, 2023): natural science is a methodical investigation of nature.…”
Section: Introductionmentioning
confidence: 99%